Are measurements of non-cholesterol sterols in plasma useful in identifying susceptibility to atherosclerosis? - Eder Carlos Rocha Quintão (Archives of Preventive Medicine - Peertechz Publications, 2023)
This review discusses the validity of plasma non-cholesterol sterols precursors of cholesterol synthesis and phytosterols in the identification of human atherosclerosis. There is an insufficient demonstration that these sterols are valid methods of measurement of cholesterol metabolism. All markers, including cholestanol, that derive from cholesterol synthesis may only reflect body retention of sterols and not necessarily increased intestinal absorption. Also, in most studies, conventional risk factors of atherosclerosis, such as obesity, diabetes mellitus, gender, and age were not taken into account.